Toll-Like Receptors Induce Signal-Specific Reprogramming of the Macrophage Lipidome - Hsieh, Wei-Yuan; Zhou, Quan D.; York, Autumn G.; Williams, Kevin J.; Scumpia, Philip O.; Kronenberger, Eliza B.; Hoi, Xen Ping; Su, Baolong; Chi, Xun; Bui, Viet L.; Khialeeva, Elvira; Kaplan, Amber; et al. (Cell metabolism, 2020)
Macrophages reprogram their lipid metabolism in response to activation signals. However, a systems-level understanding of how different pro-inflammatory stimuli reshape the macrophage lipidome is lacking. Here, we use complementary “shotgun” and isotope tracer mass spectrometry approaches to define the changes in lipid biosynthesis, import, and composition of macrophages induced by various Toll-like receptors (TLRs) and inflammatory cytokines. “Shotgun” lipidomics data revealed that different TLRs and cytokines induce macrophages to acquire distinct lipidomes, indicating their specificity in reshaping lipid composition. Mechanistic studies showed that differential reprogramming of lipid composition is mediated by the opposing effects of MyD88- and TRIF-interferon-signaling pathways. Finally, we applied these insights to show that perturbing reprogramming of lipid composition can enhance inflammation and promote host defense to bacterial challenge. These studies provide a framework for understanding how inflammatory stimuli reprogram lipid composition of macrophages while providing a knowledge platform to exploit differential lipidomics to influence immunity. [Display omitted] •A quantitative profiling of the mouse macrophage lipidome activated by immune stimuli•Macrophages alter lipid composition in a TLR-specific manner•MyD88-dependent TLRs alter lipid composition by increasing de novo MUFA synthesis•Inhibiting MUFA synthesis increases inflammation generated by MyD88-dependent TLRs Using a combination of shotgun lipidomics and stable-isotope tracing, Hsieh et al. show that distinct pro-inflammatory stimuli reshape the macrophage lipid composition in a signal-specific manner and that targeting this change can increase immunity. Thus, the study provides an in-depth resource and framework for understanding this lipidomic response while suggesting approaches for future therapy.